The Impact on Two Practising Social Workers Who Taught Social Work Students in a University Setting - Taylor, Mark; Folarin, Elizabeth; Greenchester, Alex (International Journal of Practice-based Learning in Health and Social Care, 2023)
Social Work Teaching Partnerships were developed in 2015 by the Department for Education in England to foster stronger links between social work employers and educators to improve the quality of social work graduates leaving universities. The initiative resulted in practising social workers entering universities in greater numbers to teach social work students. This paper focuses on how two practicing social workers – Elizabeth and Alex - were affected by teaching social work students in a university setting. The paper presents the practitioners’ reflections of teaching and its effects through short vignettes before examining these reflections by drawing on critical social theories. Social work teaching partnerships which encourage practitioners to spend time as social work teachers in the University classroom can produce unanticipated, positive effects for these practitioners. If the university classroom is seen as a “field” (Bourdieu, 1988), it can facilitate social workers to become objects of knowledge for social work students andto themselves. Interacting with students created opportunities for Elizabeth and Alex to reflect on their social work values, knowledge base, role, and practice. By asking unexpected questions in the classroom, students problematize (Foucault, 1984) what it means to be and to practice as a social worker. Consequently, classroom interactions with social work students can lead practitioners to think about how they would like to work. Elizabeth’s and Alex’s reflections of their classroom experiences may also help to inform and strengthen workforce retention policies in social work, as their self-efficacy increased and new possibilities for social work practice emerged.